Reply to comments by Sanjay K. Mukhopadhyay, Sucharita Pal, J. P. Shrivastava on the paper by Sial et al. (2016) Mercury enrichments and Hg isotopes in Cretaceous–Paleogene boundary successions: Links to volcanism and palaeoenvironmental impacts. Cretaceous Research 66, 60–81. (August 2017) - Sial, A.N.; Chen, Jiubin; Lacerda, L.D.; Frei, R.; Tewari, V.C.; Pandit, M.K.; Gaucher, C.; Ferreira, V.P.; Cirilli, S.; Peralta, S.; Korte, C.; Barbosa, J.A.; et al.
Abstract: One key to address the issue of the location of the K/Pg boundary at the Um Sohryngkew sections to look at Ccarb, Corg, Hg/TOC, Mo/Al chemostratigraphies, alongside Hg isotopes, in previous studied K/Pg sections in the Meghalaya area, and compare them with same type of data reported in Sial et al. (2016). The possibility of diachronic deposition cannot be totally discarded, and the K/Pg boundary could have been recorded in the Langpar Formation at one site and in the contact between the Mahadeo and Langpar formations in another. A tectonic-induced doubling of the sequence is also possible as the Meghalaya area, within the Shillong plateau, has been linked to a number of kinematic changes, including pop-up tectonics, since the Cretaceous.